The Applicability of Peer Teaching in a Post-Graduate Business Course - Montano, Vicente; Banlasan, Ma. Joycelyn (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study demonstrates the interrelation between peer teaching and six grading criteria used in a graduate business program. Twenty (20) enrolled post-graduate students in the Advanced Statistics course were assigned to five (5) peer groups participating in the study. The quantitative graphical method was used. Specifically, the Correspondence Analysis (CA) two-way contingency table describes the association between the level of peer-teaching and its applicability to the six grading criteria. Based on the CA result, there was a clear separation among the peer groupings and the six grading criteria. Peer group D find peer teaching applicable to written content and exam. Peer group B considered peer-teaching moderately applicable to research while highly applicable in language content. For students in peer group C, moderate peer teaching is highly applicable to oral content. However, peer group A regarded peer teaching as not applicable to written skills. The correspondence analysis provided valuable insights into the relationships between peer teaching and six grading criteria. This study confirms that the level of peer teaching possesses a specific level of applicability in the six grading criteria, with the peer groupings exhibiting distinct patterns.